Analysis of fluid structure interaction between fuel elements and the coolant in Xi’an Pulsed Reactor core under seismic conditions - Hu, Pan; Ma, Zhenhui; Ma, Tengyue; Wang, Baosheng; Tang, Xiuhuan; Su, Chunlei; Yang, Ning; Chen, Lixin (Frontiers in Energy Research, 2023)
The phenomenon of fluid structure interaction exists widely in nuclear facilities, and it is of great significance to the safety of nuclear facilities. Xi’an Pulsed Reactor (XAPR) is a pool research reactor with good inherent safety. It has been operating safely since the loading criticality. However, researches on fluid structure interaction have not yet been carried out on Xi’an Pulsed Reactor which was built in the 1990s because of the limitation by the technical conditions and safety evaluation range at that time. In order to fill the technical blank mentioned above, the fluid structure interaction between fuel elements and the coolant in Xi’an Pulsed Reactor core is simulated by finite element method for the first time. In this method, the interaction between solid component deformation and flow field is considered alternatively, and some results are obtained. The maximum value of the deformation of fuel elements cladding tube do not exceed 0.1 mm, and the equivalent von-Mises stress is about 4.4683 × 107 Pa under given conditions, which is less than the tensile strength and yield strength of the material. The results show that the fluid structure interaction effect between fuel elements and the coolant in Xi’an Pulsed Reactor core is very weak under the given seismic conditions, and thus will not affect the safety of the reactor core and can be ignored.